Guy of Saint-Denis and the Compilation of Texts about Music in London, British Library, Harl. MS. 281. (2008) - Mews, Constant J.; Jeffreys, Catherine; McKinnon, Leigh; Williams, Carol; ,; Crossley, John N.
No abstract available